A STUDY ON STUDENTS' HABITS IN VIEWING YOUTUBE PODCAST AND THEIR ENGLISH LISTENING SKILLS - Adzanil Prima Septy; Nabilah Putri Afifa (Language and Education Journal, 2023)
This study was to confirm a significant correlation between students' engagement with English YouTube podcasts and their listening skills. This co-relational research studied students of grade XI IPS-1 at SMAN 1 Solok Selatan of West Sumatra Province selected from some cluster random sampling technique comprising 36 students. The research employed a listening test and a set of questionnaire as to collect the data. As a result of data analysis, this research revealed a positive correlation between the intensity of students' engagement with English YouTube podcasts and their listening skills. The calculated correlation coefficient (r_calculated) for this research was 0.717, surpassing the critical value (r_table) of 0.329 at a significance level of 0.05 and degrees of freedom (df = n - 2). This indicates that the calculated correlation was higher than the critical value (0.717 > 0.329).To conclude, the research accepted the alternative hypothesis, affirming a significant correlation between students' intensity in watching English YouTube podcasts and their listening skills. Considering these findings, it is recommended that teachers incorporate YouTube podcasts into their teaching resources, creating a more engaging learning environment and motivating students to use YouTube for educational purposes, thereby enhancing their listening skills. Furthermore, students are encouraged to actively work on improving their listening skills by exploring various YouTube channels, including podcasts and other English audio resources. These efforts will contribute significantly to their language proficiency individually